2018
DOI: 10.1016/j.isjp.2018.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Significance of oxygen free radicals in the pathophysiology of hemorrhagic shock - A protocol

Abstract: HighlightsFree radicals can cause significant tissue damage.Scavengers of free radicals are a useful way to reduce reperfusion injury.Electron Paramagnetic Resonance (EPR) spectroscopy is the best way to detect free radicals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 26 publications
(28 reference statements)
0
5
0
Order By: Relevance
“…This study showed that continuous infusion of 4% albumin reduced the risk of nosocomial infections in patients in the ICU. By mixing albumin with oxidized vasostatin-1 and using a high-performance liquid chromatography (HPLC) method, it was demonstrated that albumin reduced the oxidized form of vasostatin, thereby restoring and increasing its antibacterial properties [ 2 , 3 , 6 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This study showed that continuous infusion of 4% albumin reduced the risk of nosocomial infections in patients in the ICU. By mixing albumin with oxidized vasostatin-1 and using a high-performance liquid chromatography (HPLC) method, it was demonstrated that albumin reduced the oxidized form of vasostatin, thereby restoring and increasing its antibacterial properties [ 2 , 3 , 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Common complications, that include acute respiratory distress syndrome (ARDS), acute renal failure (ARF), myocardial depression, and liver dysfunction, can occur in such a patient. This condition associated with the oxidative stress elicited in cells following ischemia or hypoxia and resuscitation known as reperfusion injury [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The excess free radicals, regardless of whether they are generated by the mitochondrial respiratory chain or NAD(p)H, can cause oxidative stress, which has a direct impact on cells. This can result in cell damage and eventually various diseases [ 6 , 7 , 8 , 9 ], such as cardiovascular diseases, cancer, neurological disorders, diabetes, ischemia/reperfusion, and aging [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ], which is also one of the risks of STI intake. In vivo, Vitamin C (VC) can react with oxygen free radicals through redox reactions, thereby neutralizing them and safeguarding the body against their damaging effects.…”
Section: Introductionmentioning
confidence: 99%
“…Free radicals are atoms, elements, compounds, or molecules that have one or more unpaired electrons in their outer orbitals [4]. These unpaired electrons are very reactive and tend to look for pairs by attacking and binding electrons to stable molecules around them [5][6][7]. The mechanism or process of free radical formation has several stages.…”
Section: Introductionmentioning
confidence: 99%